2018
DOI: 10.1002/spp2.1230
|View full text |Cite
|
Sign up to set email alerts
|

An Eocene paraclupeid fish (Teleostei, Ellimmichthyiformes) from Bolca, Italy: the youngest marine record of double‐armoured herrings

Abstract: A new double-armoured herring of the clupeomorph order Ellimmichthyiformes, Eoellimmichthys superstes gen. et sp. nov., is described herein based on a single partially complete specimen from the early Eocene Pesciara site of the Bolca Konservat-Lagerst€ atte, north-eastern Italy. The fossil documented herein exhibits a unique combination of features (e.g. ornamentation of the skull bones; medial fusion of the contralateral halves of the neural arches of abdominal vertebrae; teeth on endopterygoid, parhypural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…Three of these four characters (i.e., 2, 9, and 11) are uniquely derived characters (ci = 1) for this clade. Gasteroclupea and Sorbinichthys lie in the basal position of the Ellimmichthyiformes, but do not form sister groups as suggested by Marramà et al (2019) and Boukhalfa et al (2019). Sorbinichthyidae sensu (Murray & Wilson, 2013) including only the two Sorbinichthys species, is strongly supported by a number of derived characters: broad dorsal process of the posttemporal (15:2), posterior predorsal scutes laterally expanded (41:1), the most posterior predorsal scutes enlarged (44:1), high number of abdominal scutes (51:2), but fewer postpelvic scutes (52:1).…”
Section: Discussion Phylogenetic Relationships Of the New Formmentioning
confidence: 86%
“…Three of these four characters (i.e., 2, 9, and 11) are uniquely derived characters (ci = 1) for this clade. Gasteroclupea and Sorbinichthys lie in the basal position of the Ellimmichthyiformes, but do not form sister groups as suggested by Marramà et al (2019) and Boukhalfa et al (2019). Sorbinichthyidae sensu (Murray & Wilson, 2013) including only the two Sorbinichthys species, is strongly supported by a number of derived characters: broad dorsal process of the posttemporal (15:2), posterior predorsal scutes laterally expanded (41:1), the most posterior predorsal scutes enlarged (44:1), high number of abdominal scutes (51:2), but fewer postpelvic scutes (52:1).…”
Section: Discussion Phylogenetic Relationships Of the New Formmentioning
confidence: 86%
“…Ypresian: "Nummulitic Limestone," Bolca, Italy (Carnevale et al, 2014;Davesne et al, 2016;Marramà et al, 2019Marramà et al, , 2020; Monte Solane, Italy (Giusberti et al, 2014); London Clay Formation, United Kingdom (Friedman et al, 2016); Fur Formation, Fur, Denmark (Bonde, 1997;Bonde et al, 2008);Kapurdi Formation, Rajasthan, India (Sanhi and Choudhary, 1972;Bannikov and Tyler, 1994;Friedman and Johnson, 2005;Forey and Hilton, 2010); Cucullaea I Allomember, La Meseta Formation, Seymour Island, Antarctica (Reguero et al, 2012).…”
Section: Faunal Analysismentioning
confidence: 99%
“…The family Armigatidae was erected by Murray and Wilson (2013) to include Armigatus and Diplomystus (also see Vernygora and Murray, 2021); however, this group has not been recovered in some of the latest phyloge-netic hypotheses Marramà and Carnevale, 2016;Ribeiro, 2016, 2017;Boukhalfa et al, 2019;Marramà et al, 2019) (Figure 11). According to Murray and Wilson (2013), this family is unified by two putative synapomorphies, the distal end of uroneural 2 reaches the distal end of the uroneural 1, and the third hypural is posteriorly expanded and leaves no gap between the hypurals 2 and 3.…”
Section: Comparative Remarksmentioning
confidence: 99%
“…nov., mainly because it has no scutes bordering the trunk. Although and Marramà et al (2019) concluded that Ornategulum is a basal ellimmichthyiform based on the presence of the mesoparietal condition of the skull and the lack of the recessus lateralis (Figure 11), other authors have considered this fusiform fish is an incertae sedis species of the order Clupeiformes (Forey, 1973) or even a non-clupeomorph (Zaragüeta-Bagils 2002Boukhalfa et al, 2019).…”
Section: Comparative Remarksmentioning
confidence: 99%
See 1 more Smart Citation